Conserved DegP Protease in Gram-Positive Bacteria Is Essential for Thermal and Oxidative Tolerance and Full Virulence in Streptococcus pyogenes - Jones, C. Hal (American Society for Microbiology, 2001)
The DegP protease, a multifunctional chaperone and protease, has been shown to be essential for virulence in gram-negative pathogens such as Salmonella enterica serovar Typhimurium, Brucella abortus, Yersinia enterocolitica, and Pseudomonas aeruginosa. The function of DegP in pathogenesis appears to be the degradation of damaged proteins that accumulate as a result of the initial host response to infection, which includes the release of reactive oxygen intermediates. Additionally, the DegP protease plays a major role in monitoring and maintaining the Escherichia coli periplasm and influences E. coli pilus biogenesis. We report here the identification of highly homologous enzymes in Streptococcus pyogenes, Streptococcus gordonii, Streptococcus mutans, Staphylococcus aureus, and Enterococcus faecalis. Moreover, the phenotype of an insertionally inactivated degP allele in S. pyogenes is similar to that reported for E. coli, with temperature sensitivity for growth and enhanced sensitivity to reactive oxygen intermediates. Virulence studies in a mouse model of streptococcal infection indicate that a functional DegP protease is required for full virulence. These results suggest DegP as an attractive broad-spectrum target for future anti-infective drug development.